PENGARUH SERVICE QUALITY DAN SUSTAINBLE EVENT TERHADAP KEPUASAN PESERTA EVENT GATHERING DI BALI: IFBEC (Indonesian Food and Beverage Excutive Club/Asositaion) Bali - Firman Sinaga; I Wayan Pantiyasa (Jurnal Ilmiah Hospitality Management, 2020)
The study was concern to participants of Event Gathering in Bali especially at IFBEC (Indonesia Food and Beverage Association). This research is a quantitative study using multiple linear regression analysis and coefficient of determination analysis, using the SPSS program for windows version 2.0. with the stepwise method. The results of this study are the service quality and sustainable green event jointly positive and significant effect on satisfaction with an F value of 36.995, a significance value of 0.000 <0.05, while partially service quality has a positive and significant effect on customer satisfaction of event gathering participants in Bali especially members of the Indonesia Food and Beverage Executive Club (IFBEC) with a value of t = 6.082 significant at 0,000 (<0.05), and have a more dominant influence compared to sustainable events.